Energy cost of continuous shuttle running: Comparison of 4 measurement methods - Ciprandi, D.; Lovecchio, N.; Piacenza, M.; Limonta, E.; Esposito, F.; Sforza, C.; Zago, M. (The Journal of Strength and Conditioning Research, 2018)
Assessing runs with frequent turns (shuttle run) is a viable option to evaluate the energy cost associated with sport-specific high-intensity intermittent activities. To date, no study investigated the extent to which the computation of energy cost of exercise is affected by the following factors: procedure and duration of oxygen uptake measurement during exercise, oxygen uptake measurement during recovery, estimation of the anaerobic alactic contribution, consideration of respiratory exchange ratio (RER) in the computation, and exercise intensity. Therefore, the aim of the current study was to determine whether these factors may lead to different estimations of the energy cost of locomotion. Twenty-six healthy young men participated in two 5-m shuttle-run trials at an average speed of 50 and 75% of their maximal aerobic velocity, respectively. Oxygen uptake and lactate concentration were measured before, during, and after the trials. Results revealed that different methods of computing the energy cost of 5-m shuttle run returned significantly different results, in particular at high intensity levels. The largest significant difference found between methods was lower than 10%. This suggests that for the most accurate computation of the workload, the contribution of the anaerobic alactic mechanisms and the influence of the RER cannot be neglected. These findings might help sport scientists and conditioning trainers in identifying the exercise conditions in which including all the metabolic components are required for an accurate computation of athletes' energy expenditure. In turn, exercise conditions would be defined where the computation could be conveniently simplified without worsening results reliability.